The Molecular Mechanisms of Adaptive Response Related to Environmental Stress - Rossnerova, Andrea; Izzotti, Alberto; Pulliero, Alessandra; Bast, Aalt; Rattan, S I S; Rossner, Pavel (International journal of molecular sciences, 2020)
The exposure of living organisms to environmental stress triggers defensive responses resulting in the activation of protective processes. Whenever the exposure occurs at low doses, defensive effects overwhelm the adverse effects of the exposure; this adaptive situation is referred to as "hormesis". Environmental, physical, and nutritional hormetins lead to the stimulation and strengthening of the maintenance and repair systems in cells and tissues. Exercise, heat, and irradiation are examples of physical hormetins, which activate heat shock-, DNA repair-, and anti-oxidative-stress responses. The health promoting effect of many bio-actives in fruits and vegetables can be seen as the effect of mildly toxic compounds triggering this adaptive stimulus. Numerous studies indicate that living organisms possess the ability to adapt to adverse environmental conditions, as exemplified by the fact that DNA damage and gene expression profiling in populations living in the environment with high levels of air pollution do not correspond to the concentrations of pollutants. The molecular mechanisms of the hormetic response include modulation of (a) transcription factor Nrf2 activating the synthesis of glutathione and the subsequent protection of the cell; (b) DNA methylation; and (c) microRNA. These findings provide evidence that hormesis is a toxicological event, occurring at low exposure doses to environmental stressors, having the benefit for the maintenance of a healthy status.
Keywords: Gene Expression Regulation; adaptive response; oxidační stres; poškození DNA; Hormesis; DNA Damage; Adaptation, Physiological; hormeze; epigeneze genetická; fyziologická adaptace; Stress, Physiological; Animals; lidé; microRNA machinery; Humans; zvířata; regulace genové exprese; preventive medicine; Oxidative Stress; fyziologický stres; Epigenesis, Genetic